Comparison of volume and stand table estimates with alternate methods for selecting measurement trees in point samples. (10th September 2018) - Yang, Sheng-I; Burkhart, Harold E
Abstract: Point sampling, which does not require measuring plot area, is an efficient sampling approach for forest inventory. However, in order to estimate stand volume and stand tables, it is necessary to take tree measurements, which is the most time-consuming and labour-intensive part of the field work. In this study, we compared three methods for selecting measurement trees, including Big basal-area factor (BAF), measuring every tree on every fourth point, and randomly selecting two trees on every point. Total stand volume and stand tables were estimated in nine 37.63-ha simulated loblolly pine plantations with varying levels of spatial heterogeneity. Results indicated that all three methods performed satisfactorily for estimating stand volume. Using number of trees selected at each sample point as a weight did not show a noticeable improvement for stand volume estimation when measurement trees were randomly selected. For stand tables estimation, number of trees in small-size classes were overestimated across the three tree-selection methods when binned sample data were used. However, if the exact expansion factor computed by dbh values recorded to the nearest 0.25 cm of each sample tree (i.e. unbinned sample data) was utilized in calculation of tree frequency, measurement trees selected by Big BAF or by measuring every tree on every fourth point provided reliable estimates of stand tables.